Freshwater lichens on submerged stones and alder roots in the Polish lowlands - Mariusz Hachułka (Acta Mycologica, 2013)
The article presents the results of the studies of lichens in streams and spring areas of the escarpment zone of Wzniesienia Łódzkie Heights in Central Poland. The boulders, stones and roots of Alnus glutinosa, situated in 3 inundated zones in the streams: submerged zone, fluvial mesic zone and fluvial xeric zone, were examined in the streams. The studies have shown 23 species connected with these streams. Six species of freshwater lichens: Verrucaria aquatilis, V. hydrela, Hydropunctaria rheitrophila, V. margacea, V. praetermissa and V. madida, occupied stones in 3 different zones. Verrucaria aquatilis and Hydropunctaria rheitrophila colonized also secondary substrates – the bark of alder roots incrusted with sand grains and silt.